(untitled) (JOSAR (Journal of Students Academic Research), 2025)
This study aims to describe the perceptions of the principals and teachers of Islamic Vocational High Schools in Kanigoro regarding the Santripreneur Entrepreneurship Education Management Model for Vocational High Schools [1]. The research questions are: (1) What are the perceptions of the principals and teachers of Islamic Vocational High Schools in Kanigoro concerning the Santripreneur Entrepreneurship Education Management Model for Vocational High Schools in terms of planning, human resource organization, implementation, and evaluation? and (2) How do the principals and teachers articulate their responses to the Santripreneur Entrepreneurship Education Management Model for Vocational High Schools?This study employs a quantitative approach with a descriptive study design for the first research question and a qualitative approach with a descriptive design for the second. Quantitative data were collected using questionnaire techniques and instruments, while qualitative data were gathered through in-depth interviews guided by interview protocols. Quantitative data analysis was conducted using descriptive statistics, while qualitative data were analyzed through interactive analysis techniques. The findings of this study indicate that (1) the Santripreneur Entrepreneurship Education Management Model is acceptable and applicable in Vocational High Schools, and (2) the model received positive responses and is expected to be implemented in Vocational High Schools, provided that monitoring elements are incorporated, and shared laboratory usage is adjusted according to departmental needs.